Rapid spike in hip adduction strength in early adolescent footballers: a study of 125 elite male players from youth to senior - Light, N.; Thorborg, K.; Krommes, K.; Nielsen, M. F.; Thornton, K. B.; Hölmich, P.; Penalver, J. J. J.; Ishøi, L. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To investigate the differences in hip adductor and abductor muscle strength in elite male footballers from youth to senior level. Methods: We tested 125 players from the under-13-years (U`13) to senior squads of a Danish male professional football club in this cross-sectional design study. Hip adductor and abductor force (in newtons), torque (in newton meters), normalized torque (in newton meters per body mass), and adduction-to-abduction ratio were measured using handheld dynamometry. Results: Between U`13 and senior level, adductor force increased by 104%, torque by 127%, and normalized torque by 21%. Abductor force increased by 78%, torque by 126%, and normalized torque by 17%. For incremental differences between age groups, significant increases were observed between the ages of U`13 to U`14 (18%-39%) and U`14 to U`15 (19%-33%) for all strength measures (P = .021). No incremental difference was observed for adductor-to-abductor ratio. Conclusions: The large increases in hip adductor and abductor strength occurring between the ages of U`13 and U`15 offer insight into the strength capabilities and stress demands in these players, which may relate to injury vulnerability, and facilitate clinicians in selecting best-suited exercise interventions.